KEMANDIRIAN KEUANGAN DAERAH KOTA PEKANBARU - Sinurat, Marja; Sudrajat, Ihwan; Komedi, Komedi (Fakultas Manajemen Pemerintahan, Institut Pemerintahan Dalam Negeri, 2023)
Abstrak Analisis kemandirian keuangan daerah Kota Pekanbaru bertujuan untuk mengidentifikasi dan menganalisis berbagai faktor yang mempengaruhi kemandirian keuangan daerah melalui: struktur pendapatan daerah, belanja daerah, kebijakan perpajakan, sektor ekonomi potensial, dan upaya diversifikasi perekonomian Kota Pekanbaru. Kemandirian Keuangan Kota Pekanbaru meningkat dari tahun ke tahun yang ditujukkan dengan rasio kemandirian keuangan tahun 2020 sebesar 35,91% dengan kemampuan rendah dan pola hubungan konsultatif, tahun 2021 meningkat menjadi sebesar 41,42% walaupun masih dengan kemampuan rendah dan pola hubungan konsultatif, namun pada tahun 2022 meningkat hingga sebesar 52,64% dengan kemampuan sedang dan pola hubungan partisipatif. Hal ini menunjukkan bahwa kemandirian Kota Pekanbaru semakin lama semakin meningkat yang didukung dengan derajat desentralisasi sebesar 34,49% dengan mengubah kriteria dan rasio efektivitas pengelolaan keuangan sebesar 95,14%. Kata Kunci: Analisis Kemandirian, Kemandirian Keuangan, dan Keuangan Daerah Abstract An analysis of the regional financial independence at Pekanbaru City aims to identify and analyze various factors that affect regional financial independence through the regional income structure, regional expenditure, taxation policies, potential economic sectors, and diversifying efforts of the Pekanbaru City economy. The financial independence of Pekanbaru City increases year-on-year as indicated by the ratio financial independence from 2020 of 35.91% with low ability and consultative relationship patterns, while in 2021, that increase to 41.42% although still with low ability and consultative relationship patterns, but in 2022, increases to 52.64% with moderate ability and participatory relation patterns. The financial independence of Pekanbaru City increases from year to year as indicated by the ratio of financial independence in 2020 of 35.91% with low ability and consultative relationship patterns. In 2021, it increases to 41.42% although still with low ability and consultative relations patterns. In 2022, it will increase to 52.64% with moderate ability and participatory relationship patterns. As a result, the independence of Pekanbaru City is increasing which is supported by 34.49% by the degree of decentralization, by changing the criteria, and the effectiveness ratio of financial management of 95.14%. As a result, the independence of Pekanbaru City was growth supported by the degree of decentralization of 34.49% by changing the criteria and the ratio of financial management effectiveness of 95.14%. Keywords: Independence Analysis, Financial Independence, and Regional Financial